A new scheme of wavefield decomposed elastic least-squares reverse time migration - Lv, Wenhao; Du, Qizhen; Fu, Li-Yun; Li, Qingqing; Zhang, Jianlei; Zou, Zhen (Frontiers in Earth Science, 2022)
Elastic least-squares reverse time migration (ELSRTM) describes the reflectivity of the underground media more accurately than acoustic LSRTM in theory while suffering from the P- and S-waves crosstalk artifacts. We propose a new wavefield decomposed ELSRTM scheme to alleviate these crosstalk artifacts, which is different from conventional methods. In our new scheme, we implement the wavenumber domain elastic wavefield vector decomposition equivalently in the time-space domain to decompose source wavefield without Fourier transform, but with high precision. Then we decompose adjoint wavefield by constructing the shear component in a decoupled adjoint wave equation. Finally, based on elastic impedance parameterization, we derive the gradients with respect to elastic reflectivity in the wavefield-decomposed ELSRTM. Numerical examples show that our method is feasible even when applied to models with complex and uncorrelated P- and S-wave velocity structures.